La contribución de la energía nuclear a la solución del problema energético argentino - Alegría, Javier Luis; Csik, B .J.; Nasjleti, E. Y.; Papadópulos, C. O.; Quihillalt, Oscar A. (Naciones Unidas, 1965)
Fil: Alegría, J. L Comisión Nacional de Energía Atómica; Argentina